Education about pain and experience with cognitive-based interventions do not reduce healthcare professionals’ chronic pain - Asaf Weisman; Tomer Yona; Youssef Masharawi (PeerJ)
Background Cognitive-based interventions like pain neuroscience education (PNE), cognitive behavioral therapy (CBT), acceptance commitment therapy (ACT), and mindfulness meditation are popular for managing chronic pain. Despite their widespread adoption, evidence for their efficacy remains contradictory. Healthcare professionals (HCPs) represent a unique population to evaluate these approaches, as they possess specialized knowledge about pain mechanisms and often implement these interventions with patients. The logical premise underlying cognitive-based interventions suggests that increased knowledge and cognitive engagement with pain concepts should reduce pain intensity, making educated HCPs with chronic pain an ideal test case for this theoretical framework. Purpose To investigate whether HCPs with chronic pain who (HCPs+CP) are familiar with these methods experience less pain and improved quality of life compared to less experienced HCPs+CP and healthy HCPs (H-HCPs). Methods This cross-sectional study used an anonymous online questionnaire distributed in English through closed professional social media groups internationally. Data were collected from 550 HCPs (319 healthy, 231 with chronic pain) primarily from Israel, Canada, United States, United Kingdom, and Australia. Participants were categorized by their knowledge of pain neuroscience, experience with cognitive-based interventions, and chronic pain type (primary or secondary). Pain intensity was measured using the Numerical Pain Rating Scale, and quality of life was assessed with the World Health Organization tool the WHOQOL-BREF. Statistical analyses included Spearman’s correlation tests and independent samples t-tests. Results Pain intensity did not significantly differ between primary pain group (4.24 ± 2.21) and secondary pain group (4.37 ± 2.33) (t = −0.267, p = 0.79, Cohen’s d = −0.05). The total WHOQOL score was lower in HCPs+CP (66.81 ± 15.74) compared to healthy HCPs (71.13 ± 14.02) (t = −2.136, p = 0.035), but after removing respondents unfamiliar with interventions, no significant differences remained between groups across all WHOQOL domains (−0.09 < Cohen’s d < 0.14, p > 0.05). Among the 146 H-HCPs who had recovered from chronic pain, only 11% attributed their recovery to cognitive-based interventions, while the majority credited physical therapy (37.7%) and spontaneous recovery (32.9%). Conclusion Despite their specialized knowledge and experience with cognitive-based interventions, HCPs+CP did not report reduced pain intensity, though they maintained quality of life comparable to healthy colleagues. These findings challenge current theoretical models underlying cognitive-based pain management.